2015
DOI: 10.1140/epjb/e2015-60156-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantum dot as spin current generator and energy harvester

Abstract: Abstract. The thermoelectric transport in the device composed of a central nanoscopic system in contact with two electrodes and subject to the external magnetic field of Zeeman type has been studied. The device can support pure spin current in the electrodes and may serve as a source of the temperature induced spin currents with possible applications in spintronics. The system may also be used as an energy harvester. We calculate its thermodynamic efficiency η and the power output P . The maximal efficiency of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 79 publications
(92 reference statements)
2
15
0
Order By: Relevance
“…A similar model with ferromagnetic leads is treated in Ref. [384], but we will restrict ourselves to non-magnetic reservoirs. Then the rate equation is…”
Section: Including Spin and Double-occupancymentioning
confidence: 99%
See 1 more Smart Citation
“…A similar model with ferromagnetic leads is treated in Ref. [384], but we will restrict ourselves to non-magnetic reservoirs. Then the rate equation is…”
Section: Including Spin and Double-occupancymentioning
confidence: 99%
“…The above results, Eqs. (379)(380)(381)(382)(383)(384), constitute a complete solution of the general case of this model. Returning to the special case discussed in detail above, given by Eq.…”
Section: Solving the Steady-state Equationmentioning
confidence: 99%
“…54 It is shown that an efficient pure-spin-current injection can be used to realize the magnetization switching of a nano-scale ferromagnetic particle and measurements of room temperature spin Hall effect as well. 36,55,56 The thermoelectric transport through quantum dots [57][58][59][60] and magnetic molecules [61][62][63][64] can generate pure spin current in electrodes. It is demonstrated that the device supporting a spin current is also possible to be adopted as an energy harvester.…”
Section: Introductionmentioning
confidence: 99%
“…It is demonstrated that the device supporting a spin current is also possible to be adopted as an energy harvester. 60 Optimum conditions are realized to achieve maximum of pure spin current in the thermoelectric transport device. 65 More interestingly, it is much easier to generate highly spin-polarized and pure spin currents with a SMM attached to two normal metal electrodes in the presence of a temperature gradient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation